THE ROLE OF SISTEM ARISAN PAGUYUBAN MANAGEMENT (SIAP) IN IMPROVING THE QUALITY OF EDUCATIONAL SERVICES - Yuna, Rita; Suyanto, Suyanto; Wahyudi, M. Furqon (DIVERSITY Logic Journal Multidisciplinary, 2025)
Background. The quality of basic education services is a strategic foundation for developing superior human resources. The quality of education depends not only on the role of teachers and school facilities, but also on the extent of community involvement in the educational process. Research Purpose. This study aims to examine the role of the Sistem Arisan Paguyuban (SIAP) in improving the quality of educational services at Grebegan Public Elementary School. Research Method. The research approach used was a qualitative case study method. This research was conducted at Grebegan State Elementary School, Kalitidu District, Bojonegoro Regency. Data collection techniques included participatory observation, in-depth interviews, and documentary studies. Findings. The results showed that SIAP plays a significant role in strengthening community participation, improving infrastructure, and establishing harmonious social relations between parents and the school. SIAP can support the quality of educational services through participatory, transparent, and accountable management. Conclusion. A community-based management system can be an effective approach for enhancing the quality of education, particularly in remote areas.